Metodología Para La Evaluación Técnica De Proyectos De Infraestructura Educativa - Verdugo Bernal, Catalina Margarita; Cano Avendaño, Mariela del Carmen; Arellano Barriga, Alfonso Patricio; Balseca Sampedro, Otto Fernando; Guadalupe, Carla Sofía Arguello; Díaz Mayota, Paulina Beatriz; Granizo Paredes, Oscar Iván; Rodríguez Guerra, Juan Hugo (European Scientific Journal, ESJ, 2016)
This article describes a technical evaluation of studies or consultancies, using an adaptation of the methodology of multi-criteria analysis, usually applied in prioritization of programs and projects and evaluation of development projects. The methodology allows integration of the different criteria expressed by a group of professionals responsible for review and approval of consultancy studies used for the implementation of the country’s new Millennium Educational Units. The result of the technical evaluation of consulting with this methodology is quantitative, but qualitative variables complement our work.